Comparative Analysis of Temperature and Solar Radiation Data Available in Mubi-Northeastern Nigeria with Solar Photovoltaic Manufacturer's Standard Test Condition - Umar, Abubakar Saidu (Journal of Sustainability and Environmental Management, 2023)
In extension to the accelerated growth of the solar photovoltaic industry, the type of solar PV and reliability of solar radiation, temperature and air mass data to adopt at a particularly place has recently caught considerable attention by researchers, manufacturers, investors and consumers. Most solar panels are specified with Standard Test Condition (STC), but not all the locations are in agreement with the standard. These conditions are somehow misleading, as the values of solar radiation, temperature and air mass do not align across the full range of Earth surface. This observation encouraged the author to carryout comparative analysis to figure out whether the temperature and solar radiation data available in Mubi during 2000-2020 years align with that of manufacturer's STC specification or not. A time series analysis was adopted to compare the result obtained with STC values. It was found that the available average temperature was 28.83°C and the direct solar radiation was 3278.93W/m2 in Mubi, which was higher than the STC values. At the same time, the values are capable for harvesting efficient energy, when compared to the respective 25°C and 1000W/m2 of STC specification. The result also recommends poly-crystalline, thin-film or amorphous silicon as most suitable PV modules types to be adopted in Mubi region, because of their less tolerance to high solar radiation and temperature.Energy, Mubi, Radiation, Solar, Temperature